Studi Analisis Asuransi Syariah Terhadap Peningkatan Kesejahteraan Masyarakat - Nadia Safitri; Reva Aulia Syafira; Rika Salisa (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This study aims to analyze the influence of sharia insurance on improving community welfare. The research method used is qualitative with a descriptive explorative approach, through in-depth interviews, observations, and document studies on participants and managers of sharia insurance. The results of the study indicate that sharia insurance plays an important role in providing financial protection in accordance with sharia principles, thereby helping to reduce economic risk and increase family financial stability. Factors of financial literacy, trust in institutions, religious values, and economic capacity influence the level of community acceptance. Although there are challenges in the development of sharia insurance, large market opportunities and regulatory support pave the way for more optimal growth. In conclusion, sharia insurance contributes positively to community welfare and needs to be developed sustainably.